2012
DOI: 10.1523/jneurosci.1666-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Interactions between the Input and Output of a Songbird Cortico-Basal Ganglia Pathway Are Implicated in Vocal Sequence Variability

Abstract: Complex brain functions, such as the capacity to learn and modulate vocal sequences, depend on activity propagation in highly distributed neural networks. To explore the synaptic basis of activity propagation in such networks, we made dual in vivo intracellular recordings in anesthetized zebra finches from the input (nucleus HVC) and output (lateral magnocellular nucleus of the anterior nidopallium (LMAN)) neurons of a songbird cortico-basal ganglia (BG) pathway necessary to the learning and modulation of voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 48 publications
(86 reference statements)
4
74
0
Order By: Relevance
“…Although there exists some evidence that the AFP can influence syllable sequencing and timing (e.g., Brainard and Doupe 2001; Goldberg and Fee 2011;Hamaguchi and Mooney 2012;Ölveczky et al 2005;Scharff and Nottebohm 1991;Thompson et al 2011), we argue that the AFP is not the primary locus of adult vocal change in Bengalese finches because studies documenting AFP influences on syllable sequencing and timing also observe AFP influences on syllable structure. For example, infusions of bicuculline into LMAN increase the variability of syllable sequencing as well as the spectral entropy of individual song syllables in adult zebra finches (Hamaguchi and Mooney 2012), and inactivations of LMAN decrease sequence variability as well as the variability of syllable structure in juvenile zebra finches (Ölveczky et al 2005). Because we did not observe significant changes to the variability of syllable structure in adult Bengalese finches, our findings are inconsistent with the model that the AFP drives agedependent changes to Bengalese finch song.…”
Section: Discussionmentioning
confidence: 58%
“…Although there exists some evidence that the AFP can influence syllable sequencing and timing (e.g., Brainard and Doupe 2001; Goldberg and Fee 2011;Hamaguchi and Mooney 2012;Ölveczky et al 2005;Scharff and Nottebohm 1991;Thompson et al 2011), we argue that the AFP is not the primary locus of adult vocal change in Bengalese finches because studies documenting AFP influences on syllable sequencing and timing also observe AFP influences on syllable structure. For example, infusions of bicuculline into LMAN increase the variability of syllable sequencing as well as the spectral entropy of individual song syllables in adult zebra finches (Hamaguchi and Mooney 2012), and inactivations of LMAN decrease sequence variability as well as the variability of syllable structure in juvenile zebra finches (Ölveczky et al 2005). Because we did not observe significant changes to the variability of syllable structure in adult Bengalese finches, our findings are inconsistent with the model that the AFP drives agedependent changes to Bengalese finch song.…”
Section: Discussionmentioning
confidence: 58%
“…Although LMAN is not a layered structure with classic pyramidal cells, it shares many anatomic and physiologic similarities with the mammalian prefrontal cortex: LMAN lies anterior to motor and premotor areas, receives input from a dorsal thalamic nucleus that is not a primary sensory area, projects to the basal ganglia and to the primary song motor nucleus RA, and is more densely innervated by dopaminergic fibers than the region surrounding it (31,(60)(61)(62). Moreover, as with the prefrontal cortex, stimulation of LMAN does not evoke motor (song) output (24,46,63). Alternatively, or in addition, with respect to the hypothesis that avian nuclei are homologous to mammalian cortical layers (11,12,64), LMAN shares some but not all of the features of layer II/III intracortically connecting neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, birds expressing mHTT in area X exhibited sequencelevel changes to song, but the structure and variability of individual syllables remained unaffected. The lack of changes to previously learned syllables and the continued ability of mHTT birds to modulate variability as a function of social context further support a model in which the variability of individual syllables and of the sequences in which they occur are at least partly under independent control (16,35). A possible clinical parallel is that humans with HD often exhibit grammatical errors and can struggle to produce complex sentences, even though simple phonemic generation can be preserved (33).…”
Section: Parallels To Hd and Selective Impairment Of Sequential Movemmentioning
confidence: 75%
“…However, another intriguing possibility is that abnormal activity patterns in LMAN disrupt syllable sequences by interfering with HVC activity. Indeed, a recent study revealed an indirect pathway from LMAN to HVC that includes area X, the ventral pallidum, and a midbrain cell group (A11) (16). In this view, temporally abnormal activity patterns in LMAN can promote the production of certain syllables at wrong times in the sequence by acutely altering premotor commands at the level of HVC (Fig.…”
Section: Parallels To Hd and Selective Impairment Of Sequential Movemmentioning
confidence: 97%
See 1 more Smart Citation